Remembering social movements
1 online resource.
Keywords: "This book offers a comparative historical examination of the relations between social movements and collective memory. It examines how social movements act to shape public memory as well as how memory plays an important role within social movements through 15 historical case studies that ensure the reader gains a real insight into the remembrance of social activism across the globe and in different contexts. Bringing together the fields of Memory Studies and Social Movement Studies, this book systematically scrutinises the two-way relationship between memory and activism and uses case studies to ground students while offering analytical tools for the reader"--